2022
DOI: 10.3390/foods11243987
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Climate Change on Food Crop Production in Lagos State

Abstract: Climate change is set to be particularly disruptive in poor agricultural communities. This study examines the effects of, and farmer’s perceptions of, climate change on farming practices for cassava and maize in Lagos, Nigeria. Analysis of weather data from 1998 to 2018 (the most recent available) reveals little impact on cassava yield but a significant impact on maize yield. Furthermore, survey results indicate that farmers in this area are currently implementing techniques to adapt to changes in climate base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The normalized difference water index (NDWI) and its intensity indicate vegetation responses to water availability in the ecosystem (soil and air) Water was more available during the year 2017 compared to 2018 and 2019 during the rainy season. Adebayo, [37] and Tajudeen [38] reported the importance of rainfall to crop productivity. Mosunmola et al, [39] and Farmsquare [40] reported the effects of rainfall variables such as onset, cessation and length of growing season on agricultural productivity.…”
Section: Effect Of Land Use and Season On Vegetation Indicesmentioning
confidence: 99%
“…The normalized difference water index (NDWI) and its intensity indicate vegetation responses to water availability in the ecosystem (soil and air) Water was more available during the year 2017 compared to 2018 and 2019 during the rainy season. Adebayo, [37] and Tajudeen [38] reported the importance of rainfall to crop productivity. Mosunmola et al, [39] and Farmsquare [40] reported the effects of rainfall variables such as onset, cessation and length of growing season on agricultural productivity.…”
Section: Effect Of Land Use and Season On Vegetation Indicesmentioning
confidence: 99%
“…In addition, erroneous agricultural practices degrade soil quality and reduce agricultural productivity. Idumah et al [ 24 ] and Tajudeen et al [ 25 ] emphasize that the impact of climate change on food production in Nigeria could increase in the coming years, as more than 80% of crop production depends on rainfall. The Notre Dame Global Adaptation Initiative [ 26 ] reports that Nigeria is the 53rd most vulnerable country and the 6th least prepared country in the world in terms of adapting to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Farmers' difficulties and challenges of climate change are crucial to planning relevant policies for adaptation strategies to climate change (Ali et al, 2021). By this means, the anticipated adverse effects of climate change can be reduced through abilities to exchange information, ideas and feedback in both policy and scientific work are important for climate projections that reduces climate change effects (Tajudeen et al, 2022 andNabara et al, 2023).…”
Section: Introductionmentioning
confidence: 99%